Resilient SDN Intercontroller Network Design under Availability Requirements and Geodiversity Constraints - Santos, Dorabella (2022)
In Software-Defined Networking (SDN), the data plane is defined by the switches which are connected to a set of controllers defining the control plane. The intercontroller connections have lacked the same focus in the literature as the switch-controller connections, despite the set of logically centralized controllers being the brain of the SDN network. In this paper, we address a bi-objective joint optimization problem involving the controller placement problem, geodiversity and intercontroller availability guarantees. The availability guarantees imply a subgraph whose links can be upgraded at a given cost. The geodiversity constraints extend robustness to disaster-based failures. To solve this NP-complete non-linear problem, we employ a heuristic strategy based on the decomposition into manageable subproblems.